2016
DOI: 10.1007/978-1-4939-6707-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Species and Their Associated Mycotoxins

Abstract: The genus Fusarium includes numerous toxigenic species that are pathogenic to plants or humans, and are able to colonize a wide range of environments on earth. The genus comprises around 70 well-known species, identified by using a polyphasic approach, and as many as 300 putative species, according to phylogenetic species concepts; many putative species do not yet have formal names. Fusarium is one of the most economically important fungal genera because of yield loss due to plant pathogenic activity; mycotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(141 citation statements)
references
References 179 publications
1
129
1
10
Order By: Relevance
“…The metabolites from F. chlamydosporum were aurofusarin, chlamydospordiol and W493B ( Table 1). Contrary to expectations (Shier and Abbas, 1992;Solfrizzo et al, 1994;Munkvold, 2016), chlamydosporol was not found in the cultures of this species in our present study. For the F. incarnatum/equiseti species complex, chrysogin, deoxyfusapyron, fusapyron and equisetin were detected.…”
Section: Metabolites From Fusarium and Tolypocladiumcontrasting
confidence: 99%
“…The metabolites from F. chlamydosporum were aurofusarin, chlamydospordiol and W493B ( Table 1). Contrary to expectations (Shier and Abbas, 1992;Solfrizzo et al, 1994;Munkvold, 2016), chlamydosporol was not found in the cultures of this species in our present study. For the F. incarnatum/equiseti species complex, chrysogin, deoxyfusapyron, fusapyron and equisetin were detected.…”
Section: Metabolites From Fusarium and Tolypocladiumcontrasting
confidence: 99%
“…Previous studies have already optimized specific PCR assays to detect Fusarium species that are mycotoxin-producing or pathogens of maize [17,29]. However, the new taxonomic changes and/or the description of new Fusarium species of interest in relation to maize [50,51] have supposed that some of these previously described methods gave unspecific results. Therefore, in this work, we have developed and optimized new protocols to detect and identify F. graminearum, F. langsethiae, F. fujikuroi, F. poae, F. sporotrichioides and F. temperatum, using pure DNA or direct maize samples, and we also have modified the PCR conditions in the case of F. subglutinans to ensure the specific amplification using the primers described by Scauflaire et al (2012) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium species are toxigenic and pathogenic to plants or humans, and the trichothecenes and the fumonisins produced by them are the most well-known mycotoxins [ 6 ]. Fumonisins (FUMs) were first isolated from F. moniliforme in 1988 [ 7 ], and they can be produced by other Fusarium species such as F. verticillioides , F. proliferatum and F. nygamai [ 8 ].…”
Section: Introductionmentioning
confidence: 99%